Effect of cold work and overload on fatigue life of notched 2024-T351 aluminium alloy specimens - Arora, Prithvi Raj, Assoc. Prof. Dr.; Tan, Jeffrey Meng Lee; Prasetyo, Edi; M., Saleem (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/